TMEM16A/ANO1 calcium-activated chloride channel as a novel target for the treatment of human respiratory syncytial virus infection. Issue 1 (27th October 2020) - Pearson, Hayley; Todd, Eleanor J A A; Ahrends, Mareike; Hover, Samantha E; Whitehouse, Adrian; Stacey, Martin; Lippiat, Jonathan D; Wilkens, Ludwig; Fieguth, Hans-Gerd; Danov, Olga; Hesse, Christina; Barr, John N; et al.
Abstract : Introduction: Human respiratory syncytial virus (HRSV) is a common cause of respiratory tract infections (RTIs) globally and is one of the most fatal infectious diseases for infants in developing countries. Of those infected, 25%–40% aged ≤1 year develop severe lower RTIs leading to pneumonia and bronchiolitis, with 10% requiring hospitalisation. Evidence also suggests that HRSV infection early in life is a major cause of adult asthma. There is no HRSV vaccine, and the only clinically approved treatment is immunoprophylaxis that is expensive and only moderately effective. New anti-HRSV therapeutic strategies are therefore urgently required. Methods: It is now established that viruses require cellular ion channel functionality to infect cells. Here, we infected human lung epithelial cell lines and ex vivo human lung slices with HRSV in the presence of a defined panel of chloride (Cl − ) channel modulators to investigate their role during the HRSV life-cycle. Results: We demonstrate the requirement for TMEM16A, a calcium-activated Cl − channel, for HRSV infection. Time-of-addition assays revealed that the TMEM16A blockers inhibit HRSV at a postentry stage of the virus life-cycle, showing activity as a postexposure prophylaxis. Another important negative-sense RNA respiratory pathogen influenza virus was also inhibited by the TMEM16A-specific inhibitor T16Ainh-A01. Discussion: These findings reveal TMEM16A as an exciting target for future host-directed antiviral therapeutics.